Respon Pertumbuhan Setek Tunas Tangkai Bunga Melati Air (Aquarius palifolius) pada Berbagai Jenis Media Tanam - Rina Alfina; Olivia Darlis; Rizki Rizki; Rasdanelwati Rasdanelwati (Syntax Idea)
Research on the growth of water jasmine stem cuttings in various planting media aims to study the response of water jasmine stem cuttings to different planting media and obtain the best planting medium for the growth of water jasmine stem cuttings. The experiment uses a Completely Randomized Design (CRD) with 4 treatment groups of planting media and 5 replications, resulting in 20 experimental units. The planting media used as treatments are paddy soil, paddy soil + chicken manure fertilizer, paddy soil + cow manure fertilizer, and paddy soil + burnt rice husk. Growth parameters observed include percentage of growth, plant height, and the number of leaves. Based on the research results, it can be seen that the growth of water jasmine stem cuttings showed significantly different responses when planted in various types of media. The best planting medium to accelerate the growth of water jasmine stem cuttings is paddy soil + cow manure fertilizer, with greater plant height and leaf count compared to the other three treatments.